2012
DOI: 10.1111/j.1532-950x.2012.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Approach to the Subextensorius Recess of the Lateral Femorotibial Joint of the Foal

Abstract: The subextensorius recess may be safely accessed arthroscopically in foals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that sepsis of the LFTJ usually occurs as an extension of infection from the FPJ, as the two communicate in 1-17% of cases (Reeves, Trotter and Kainer, 1991;Vacek, Ford and Honnas, 1992;Hennessy et al , 2012). In this case series, only one of the three foals was presented with additional joints affected in the stifle (Foal 2), with the other two foals having only LFTJ involvement.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been reported that sepsis of the LFTJ usually occurs as an extension of infection from the FPJ, as the two communicate in 1-17% of cases (Reeves, Trotter and Kainer, 1991;Vacek, Ford and Honnas, 1992;Hennessy et al , 2012). In this case series, only one of the three foals was presented with additional joints affected in the stifle (Foal 2), with the other two foals having only LFTJ involvement.…”
Section: Discussionmentioning
confidence: 68%
“…The stifle is a commonly-reported site for sepsis in foals (Wrightet al , 2017;O'Brien et al , 2021). Compared to other stifle compartments, sepsis of the lateral femorotibial joint (LFTJ) is relatively rare (Reeves, Trotter and Kainer, 1991;Vacek, Ford and Honnas, 1992;Hennessy et al , 2012). It has been estimated that up to 1% of all foals, and 13% of those in neonatal intensive care, are affected by septic arthritis and osteomyelitis (McIlwraith, 1983;Martens, Auer and Carter, 1986;Richardson DW and Stewart S, no date).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that sepsis of the LFTJ usually occurs as an extension of infection from the FPJ, as the two communicate in 1%–17% of cases (Hennessy et al., 2012; Reeves et al., 1991; Vacek et al., 1992). In this case series, only one of the three foals was presented with additional joints affected in the stifle (Foal 2), with the other two foals having only LFTJ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The stifle is a commonly reported site for sepsis in foals (O'Brien et al., 2021; Wright et al., 2017). Compared to other stifle compartments, sepsis of the lateral femorotibial joint (LFTJ) is relatively rare (Hennessy et al., 2012; Reeves et al., 1991; Vacek et al., 1992). It has been estimated that up to 1% of all foals, and 13% of those in neonatal intensive care are affected by septic arthritis and osteomyelitis (Martens et al., 1986; McIlwraith, 1983; Richardson & Stewart, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, diagnostic arthroscopy had been reported as the ‘gold standard’ for diagnosing stifle disorders (Adrian et al ). Although different dorsal (Moustafa et al ; Boening ; McNally et al ; Hennessy et al ) and caudal approaches (Watts and Nixon ) and techniques under sedation (Frisbie et al ) have been described, great portions of the stifle still remain technically inaccessible due to anatomic limitations (Adrian et al ). Recently, a combination of ultrasonography and arthroscopy was suggested to overcome these boundaries and to best evaluate stifle pathology (Barrett et al ; Adrian et al ).…”
Section: Discussionmentioning
confidence: 99%